Evaluasi Autentik dalam Pembelajaran Reading: Menilai Pemahaman secara Kontekstual - Dian Nashrul Munif; Aries Fachriza; Diska Fatima Virgiyanti; Dinar Dipta; Eka Indah Nuraini (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
Authentic evaluation is an assessment approach that emphasizes high-level thinking skills and students' ability to complete meaningful tasks that reflect real-world situations. In the context of reading learning in English, it is an important alternative to overcome the limitations of traditional evaluations that tend to only measure literal understanding. This study aims to describe the application of authentic evaluation in reading learning and identify the forms, strategies, and challenges of its implementation in a secondary school environment. This study applied a descriptive qualitative approach with English teachers and students as research subjects in a junior high school. Data collection techniques through in-depth interviews, direct observation, and documentation of the assessment instruments used. Data analysis used the Miles and Huberman model including the stages of data reduction, data presentation (data display), and drawing conclusions/verification. The results of the study showed that teachers implemented authentic evaluation in various forms, such as text summaries, reading journals, written critical responses, and reading-based presentations. This was able to improve contextually students' reading comprehension in depth. However, several obstacles were found, such as time constraints and the need for objective assessment instruments. Strategies such as the use of rubrics and gradual training for students have proven effective in overcoming these obstacles. This study emphasizes the importance of authentic evaluation as a more meaningful assessment approach in learning reading.